The alteration of renal function in sepsis and septic shock patients in pediatric intensive care unit - Feiby Julianto; Adrian Umboh; Suryadi Tatura (Paediatrica Indonesiana, 2011)
Background Sepsis is a commonly seen emergency case in the pediatric intensive care unit.1 Severe sepsis mortality rate in developed country andin developing country such as Indonesia are 9% and 50-70%, respectively. Furthennore, the mortality rate in septic shock is 80%.2 Several researches documented increasing rate of acute kidney injury (AKI) incidence correlated 'With sepsis. Clinical intervention identification may decrease AKI and sepsis incidence.Objective To identify the correlation between incidence of AKI in sepsis and in septic shock patients who was treated in pediatric intensive care unit (PICU).Methods A cross sectional study was perfonned in 37 patients diagnosed as sepsis according ACCP/SCCM criteria for children aged 1 month to 13 years. The study was conducted in Pediatric Department, Prof. Dr. R.D. Kandou hospital from April 2009 to June 2009.Results From 37 sepsis patients, 27 were boys and 10 were girls. In the sepsis group (n=27) 10 had AKI, and in the septic shock group (n= 10) had AKI. Phi correlation coefficient applied to statistically analyzed sepsis in correlation with AKI (creatinin serum and GFR). Significant Phi correlation coefficient was (r=0.117; P> 0.05)Conclusions The study concludes that there is no correlation of renal function impainnent Mth sepsis and septic shock.